ALL MOS low-power low-voltage LDO with an embedded voltage reference - Chandra, Bernardus Edwin (2018)
The Low Drop-out Voltage (LDO) regulators are widely used in present electronic industry. Such voltage regulator is one of the subsystems in the power management unit. This LDO consumes very little current and will be designed in a 0.18µm CMOS technology. The minimum unregulated input voltage, Vin, is typically 1.2 voltage, and the output voltage is an unscaled temperature compensated voltage in a voltage-mode approach derived from summing the PTAT and CTAT components, generated from transistors operating in the sub-threshold region of operation.